TECHNOLOGY FOR THE USE OF MULTIMEDIA TECHNOLOGY IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Yakubova Manzura (Web of Journals Publishing, 2024)
This article provides methodological recommendations for the implementation of multimedia technology in the educational process in preschool education.
Keywords: innovation, multimedia technology, free thinking, development of the child's thinking, modern tools, scientific potential, individuality.